Peramalan Bisnis Unit Usaha Syariah PT ABC dalam Tantangan Spin Off - Tatang Nurhidayat (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2021)
Spin off is separation of the sharia unit into a new company independent from its conventional parent. Spin off is a strategic issue for sustainability and development of Islamic financial institutions including Sharia Insurance. Independence and focus on the spin off process are positive. However, the economies of scale for stability and sustainable growth become challenges. The problem observed in this study is the ability of the general insurance sharia business unit to fulfill the spin off obligation as mandated in the Insurance Act number 40 of 2014. This Act stated that at the latest in 2024 it has to be spinned off by submitting a business plan to OJK no later than 2020. This study use Time Box Box method-Jenkins (ARIMA). The results of this study are expected to be consideration factor and information for General Insurance Companies, especially PT ABC, in determining the spin off business plan using forecasting.